TRAIL EULER MINIMAL DI DALAM GRAF BERARAH YANG TERBOBOTI - Siti Julaeha; Murtiningrum Murtiningrum; Rida Novrida; Endang Retno Nugroho (JURNAL ISTEK, 2011)
Suppose G is a Eulerian directed graph with an edge labeling. In this paper will discuss the literature studies an algorithm to construct Euler trail that starts at a node r with the lexicographic minimum label among all Euler trail that starts node r is.